Beyond Immersion: A Comparative Analysis of Cognitive Learning Outcomes in Augmented Reality (AR) versus Traditional Laboratory Settings - Ravi Dara; Roya Zahir; Jamil Khan (Journal Emerging Technologies in Education, 2025)
Background. The integration of Augmented Reality (AR) in education has garnered attention for its potential to enhance student engagement and learning outcomes. While much of the research focuses on the immersive nature of AR, its impact on cognitive learning outcomes compared to traditional laboratory-based learning environments remains underexplored. Purpose. This study aims to compare the cognitive learning outcomes of students who engage with content in AR environments versus those who participate in traditional laboratory settings. The research seeks to determine whether AR offers significant advantages in terms of knowledge retention, problem-solving, and conceptual understanding. Method. A mixed-methods design was employed, combining quantitative pre- and post-test assessments to measure cognitive outcomes and qualitative focus group discussions to capture students' experiences. The study involved 200 students, with 100 participating in AR-based learning and 100 in traditional laboratory settings. Results. The AR group showed a greater improvement in cognitive learning outcomes (23% increase) compared to the traditional laboratory group (14% increase). Students in the AR environment also reported higher levels of engagement, which correlated with their cognitive improvements. Conclusion. AR-based learning environments offer significant cognitive benefits over traditional laboratory settings, particularly in enhancing conceptual understanding and problem-solving skills.